Sistem Informasi Berbasis Website Sebagai Media Promosi Sekaligus Layanan Pemesanan Yang Dikembangkan pada UMKM Omah Batik - Muhammad Dicho Nugroho Wicaksono (Jurnal Ilmiah Informatika, 2024)
This research describes the development of a website-based information system as a promotional media and ordering service for Omah Batik Sukun UMKM using the waterfall methodology. UMKM Omah Batik Sukun is a community business group located at Jalan S. Supriadi 2C No. 14 Sukun, Malang City, East Java. established in 2015 and started community strengthening activities in 2018. UMKM Omah Batik Kinanti itself comes from the Tourism Awareness Group, also known as POKDARWIS in the RW 03, and has expertise and interest in the batik making process. Since its inception, this business has not experienced much progress. One of the reasons is that there is no media or platform that can be used to launch and market products and display what UMKM Omah Batik Sukun is. Therefore, in this final project research, researchers designed an information system that functions as an advertising tool and manufacturing product ordering service. We hope that this website can become a platform for information and help the wider community to find out more about what UMKM Omar Batik Sukun is.